Diseño y Construcción de un Tablero Didáctico de instalación Eléctrica con Capacidad de carga 45 KVA (2022)
This project is focused on the supply of a didactic electric board to necessary practices in the laboratory of the electromechanics faculty of the strengthen the Antonio Nariño University in Villavicencio, in order to have knowledge about the condition of the laboratory is necessary to know the requirements formation.